STUDY OF SOLID AND MICROPLASTIC WASTE IN THE LEAVE LINE IN SANDY SEDIMENTS ON BOCA DA BARRA BEACHES AND CAMPAS BEACH - TAMANDARÉ-PE - Gabriele, Emily; Varjão, Débora; Danielly, Maiara; Barbosa, Edinilson; Maria, Adriana (Journal of Interdisciplinary Debates, 2022)
Microplastics have been a topic commonly discussed in recent times due to the damage they cause to the environment, whether marine or terrestrial. Currently, the exposure of the microplastic problem has been alarming, which causes the study of these residues on a large scale, however, a precise methodology has not yet been obtained to quantify these residues. The study was carried out on the beaches of Boca da Barra and Praia de Campas, Tamandaré-PE, the collection was carried out during high tide and full moon on the left line, four samples were collected at each point, being point 1 (Boca da Barra) and point 2 (Praia de Campas), both beaches with different profiles in relation to human actions, the beach of Boca da Barra with less human actions compared to Praia de Campas that receives more tourists. Subsequently taken to LAGES (Laboratory of Sedimentology and Paleontology) to quantify and qualify the solid and microplastic residues of the appropriate samples. At the end of the samples, the difference in the amount of microplastic from one beach to the other is evident. Being the beach of Boca da Barra with a lower incidence in relation to Praia de Campas.